Effectiveness of non-pharmaceutical measures in preventing pediatric influenza: a case–control study - Torner, Núria (BMC Public Health, 2015)
BACKGROUND: Hygiene behavior plays a relevant role in infectious disease transmission. The aim of this study was to evaluate non-pharmaceutical interventions (NPI) in preventing pediatric influenza infections. METHODS: Laboratory confirmed influenza cases occurred during 2009–10 and 2010–11 seasons matched by age and date of consultation. NPI (frequency of hand washing, alcohol-based hand sanitizer use and hand washing after touching contaminated surfaces) during seven days prior to onset of symptoms were obtained from parents of cases and controls. RESULTS: Cases presented higher prevalence of underlying conditions such as pneumonia [OR = 3.23; 95 % CI: 1.38 – 7.58 p = 0.007], asthma [OR = 2.45; 95 % CI: 1.17 – 5.14 p = 0.02] and having more than 1 risk factor [OR = 1.67; 95 % CI: 0.99 – 2.82 p = 0.05]. Hand washing more than 5 times per day [aOR = 0.62; 95 % CI: 0.39 – 0.99 p = 0.04] was the only statistically significant protective factor. When considering two age groups (pre-school age 0–4 yrs and school age 5–17) yrs , only the school age group showed a negative association for influenza infection for both washing more than 5 times per day [aOR = 0.47; 95 % CI: 0.22 – 0.99 p = 0.04] and hand washing after touching contaminated surfaces [aOR = 0.19; 95 % CI: 0.04 – 0.86 p = 0.03]. CONCLUSION: Frequent hand washing should be recommended to prevent influenza infection in the community setting and in special in the school age group.